Stan, potrzeby i perspektywy badań nad dziejami diecezji ełckiej, cz. 2: Lud Boży i Aktywność Kościoła - Guzewicz, Wojciech (Civitas et Lex, 2021)
The article presents the state of research on the history of the Ełk diocese in relation to the prosopography of the clergy and lay faithful. The historiographic review was made on the basis of approx. 200 scientific and popular science publications.